If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1x + -1(-2) + -8 + 4x = 0 Multiply -1 * -2 10 + -1x + 2 + -8 + 4x = 0 Reorder the terms: 10 + 2 + -8 + -1x + 4x = 0 Combine like terms: 10 + 2 = 12 12 + -8 + -1x + 4x = 0 Combine like terms: 12 + -8 = 4 4 + -1x + 4x = 0 Combine like terms: -1x + 4x = 3x 4 + 3x = 0 Solving 4 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 0 + -4 3x = 0 + -4 Combine like terms: 0 + -4 = -4 3x = -4 Divide each side by '3'. x = -1.333333333 Simplifying x = -1.333333333
| 16.7x=79.49 | | 3/5x-4=12 | | 4y=-9x | | 65/2 | | (y-7)(y-7)(y-7)=6 | | v+10=-1 | | 8316=(14784)r(9) | | 4x-6(2x-3)= | | -7+4m=-5+6m | | 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 | | ab-4a-4b+8=0 | | 5a+(-7)=-2 | | 4k-7+16=-3 | | 5x+20=24-3x-12 |